Behavior and physiology of boars housed in three different environments - Bernardino, Thiago; Sabei, Leandro; Parada Sarmiento, Marisol; Sato, Denis; Farias, Sharacely de Souza; Paula, Tauana Maria Carlos Guimarães de; Marques, Gabriela Rezende; Zanella, Adroaldo José (Frontiers in Ethology, 2025)
Boars housed in commercial conditions are often housed in pens or in individual crates, and are subjected to low-stimulus environments, which may affect the expression of normal species-specific behaviors and compromise its health and welfare. Breeding boars’ behaviors has been poorly reported in the scientific literature, as well as their physiology and its circadian rhythm of cortisol. Moreover, an environmental enrichment for breeding boars, as far as we know, has not been studied or reported in literature, lacking its impact on how it can improve their welfare. Thus, we aimed to evaluate the behavior and salivary cortisol physiology of breeding boars housed in three different conditions: crates, pens and enriched pens. For the enriched pens the boars were brushed, they were showering and they received hay, twice daily. All animals were video recorded, and we collected saliva samples in the morning and afternoon to measure the circadian rhythm of cortisol. The boars housed in crates showed more (5.23 seconds) abnormal behaviors (head weaving, biting bars, licking floor, sham-chewing, drinker manipulation, and licking empty trough) than boars housed in pens (2.47 seconds) and in enriched pens (2.93 seconds). In addition, the boars housed in the enriched pens did have significant differences in salivary cortisol through the day (morning and afternoon assessment), different from boars from other treatments. We demonstrated that breeding boars that received environmental enrichment showed indicators of better welfare (behavior and salivary cortisol ratio), suggesting that this strategy should be considered as a protocol to improve their welfare.